Socio-Semiotic Analysis of Newspaper Cartoons on COVID-19 (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2024)
This work investigated socio-semiotic analysis of newspaper cartoons on COVID-19. This study was borne out of the need to understand how different layers of meanings are enacted in COVID-19 cartoons. Specifically, this study sought to understand the socio-semiotic features embedded newspaper cartoons on COVID-19. This study took a critical look at the degree of abstraction and vocabulary affected the readability of newspaper cartoons on COVID-19. Also, the messages and the ideologies embedded in cartoons on COVID-19 as well as the socio-semiotic relevance of the selected COVID-19 cartoons towards the discourse of COVID-19 pandemic in Nigeria were thoroughly investigated. Kress and van Leewan Visual Social Semiotics Theory and cooperative Principle Theory formed the theoretical framework of this study. The textual data for this study were drawn from selected newspapers.  The choice of these cartoons was based on the simplicity of the message embedded in the cartoons. This study discovered that newspaper cartoons on COVID-19 used multimodal used include texts, icons, and symbols to enact meaning in their campaign against the spread of COVID-19. The cartoons used caricature and satire to lampoon and criticize the government on their uncoordinated and corrupt oriented response towards the management of COVID-19 pandemic. It was also discovered that cartoonist used short sentences in the framing of their messages which were apt and straight-to-the-point.
Keywords: COVID-19; socio-semiotic; cartoons; multimodality; socio-semiotic relevance; readability